2018
DOI: 10.1093/ejcts/ezx503
|View full text |Cite
|
Sign up to set email alerts
|

Aortic elongation in aortic aneurysm and dissection: the Tübingen Aortic Pathoanatomy (TAIPAN) project†

Abstract: Patients with ectatic (45-54 mm diameter) and elongated (≥120 mm) ascending aortas represent a high-risk subpopulation for TAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 18 publications
0
28
1
1
Order By: Relevance
“…Without mentioning the difference between bicuspid and tricuspid aortic valves, Krüger and colleagues published several articles linking the incidence of aortic dissection with the length of the ascending aorta (Krüger et al, ), allowing them to establish a dissection risk score in the TAIPAN project (Krüger et al, ). Without assessing the risk of dissection, we identified differences in the ascending aortic lengths between our two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Without mentioning the difference between bicuspid and tricuspid aortic valves, Krüger and colleagues published several articles linking the incidence of aortic dissection with the length of the ascending aorta (Krüger et al, ), allowing them to establish a dissection risk score in the TAIPAN project (Krüger et al, ). Without assessing the risk of dissection, we identified differences in the ascending aortic lengths between our two groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation that the entrance of the aortic dissection mostly extends in a circumferential direction could be explained by decreased longitudinal elasticity due to aortic elongation (53,88). Meanwhile, a previous study also showed that the length of the AAEs aorta processed from 3D reconstruction based on CTA is significantly larger than the non-AAEs aorta (7,78). These findings led to further investigation into the correlation, if any, between aortic length and the risk of AAEs (Figure 1) (7,78).…”
Section: Aortic Lengthmentioning
confidence: 96%
“…Thus, as the centerline method increasingly used, it may be necessary to ''left-shift'' the thresholds (30). Furthermore, there is also a method of calculating the diameter based on the circumference to minimize the influence of the non-circular aorta (7,31). The above evidence suggests that a unified acquisition protocol and general morphological parameters should be developed to eliminate heterogeneity caused by different measurement methods (22).…”
Section: Absolute Aortic Diameter As An Indicatormentioning
confidence: 99%
“…Recent publications have focused on identifying new morphological predictors or morphological risk factors with the purpose to improve screening and prevention of AAAD since the simple reduction of the maximum aortic diameter cut-off value would not necessarily imply a net benefit in terms of mortality (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%